Infocracia e Psicopolítica em Byung-Chul Han - Leandro Chevitarese (O Que Nos Faz Pensar)
The characterization of the Performance Society elaborated by Byung-Chul Han points to the emergence of new power dynamics and subjectivation processes, in line with the demands of contemporary capitalism mediated by digital information and surveillance technologies, operationalized by artificial intelligence algorithms. This article investigates the challenges for contemporary democracy, which moves towards infocracy and psychopolitics, presenting the perspectives of a politics of inactivity and an ethics of alterity as ways of confronting the digitalization of life.